2009
DOI: 10.1038/jes.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to perfluorinated acids and fetal growth

Abstract: The widespread detection of perfluorinated acids (PFAs) in humans and known developmental toxicity in animals has raised concern about their potential effects on human reproductive health. Our objective was to determine whether increasing maternal exposure to PFAs is associated with adverse effects on fetal growth and length of gestation in women giving birth in Alberta, Canada. We examined the concentrations of perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), and perfluorohexane sulfonate (PFH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 24 publications
(51 reference statements)
8
115
5
Order By: Relevance
“…Also a British study found that girls born to mothers with maternal serum concentrations of PFOA in the upper tertile weighed less (130 g (95%CI: -237, -30)) at birth compared with girls born to mothers with serum concentrations in the lower tertile (Maisonet et al, 2012). Contrary to the above findings, 2 smaller Canadian studies found no evidence of decreased birth weight and maternal PFOA levels (Monroy et al, 2008;Hamm et al, 2010). In summary, in general Nordic and British studies suggest that PFOA affects the foetal growth negatively, whereas smaller Canadian studies did not see this effect.…”
Section:  Developmental Outcomecontrasting
confidence: 42%
See 3 more Smart Citations
“…Also a British study found that girls born to mothers with maternal serum concentrations of PFOA in the upper tertile weighed less (130 g (95%CI: -237, -30)) at birth compared with girls born to mothers with serum concentrations in the lower tertile (Maisonet et al, 2012). Contrary to the above findings, 2 smaller Canadian studies found no evidence of decreased birth weight and maternal PFOA levels (Monroy et al, 2008;Hamm et al, 2010). In summary, in general Nordic and British studies suggest that PFOA affects the foetal growth negatively, whereas smaller Canadian studies did not see this effect.…”
Section:  Developmental Outcomecontrasting
confidence: 42%
“…Two other smaller Canadian studies did not find any associations between maternal PFHxS levels and fetal weight and length of gestation (Hamm et al, 2010;Monroy et al, 2008). A study examined the association between PFCs and ADHD among children in the US (Hoffman et al, 2010).…”
Section:  Developmental Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…PFOS, PFOA, PFNA and PFHxS, and indices of foetal growth/development, including birth weight, birth length, ponderal index, gestational age, and pre-term birth, have been conflicting. Some have shown increased levels to be inversely related (Andersen et al, 2010;Apelberg et al, 2007;Fei et al, 2007;Wu et al, 2012;Darrow et al, 2013, Maisonet et al, 2012Wang et al, 2011), whereas others have reported no effect or an opposite association (Fei et al, 2008b, Hamm et al, 2010Olsen et al, 2009).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%